PENGARUH POLA ASUH ORANG TUA TERHADAP KETERLAMBATAN BERBICARA PADA ANAK USIA 5-6TAHUN DI TK IT CAHAYA PELANGI - Khanifah, Maulida Nur (Pelangi Jurnal Pemikiran dan Penelitian Islam Anak Usia Dini, 2026)
The influence of parenting patterns on speech delays in group B children aged 5-6 years at Cahaya Pelangi IT Kindergarten. Maulida. Children's speaking ability has not developed well, it is seen that many children have difficulty in understanding commands. This is due to the lack of parental ability in creating communication relationships with children and also environmental factors. The purpose of this study was to determine how much influence parenting patterns have on speech delays in group B children aged 5-6 years at Cahaya Pelangi IT Kindergarten. The research method used a quantitative approach with a linear regression method with a sample of 16 children. Data collection techniques used observation and documentation. Data analysis techniques were to determine the influence of parenting patterns as variable X and speech delays as variable Y, data were analyzed using SPSS version 25. The results of the study showed that children's speaking ability was due to the lack of parental ability in creating communication relationships with children and also environmental factors. The influence of parenting patterns on speech delays in group B children aged 5-6 years at Cahaya Pelangi IT Kindergarten was very significant with the results of F count (5.428) > F table (4.60)